The Zero superlative ʾafʿal: A Semantic Analysis of the Noble Qur’an - Lutf, Sadeq Mus’aid (Arab Journal for Sciences and Research Publishing, 2019)
This study aims to highlight one of the features of the superlative ʾafʿal. In some cases, it may be devoid of preference. The researcher used an inductive qualitative approach for its suitability to the scope and purpose of the current study. The study concluded that the superlative ʾafʿal is of two types. The first type refers to two things that share a common quality/adjective. The other type, on the other hand, can be called the zeroʾafʿal superlative asit refers to two things that do not share a common adjective or quality. The study recommend that further studies need to be conducted with a view to investigating this grammatical issue in the Noble Qur’an and in literary sources as well.